The Dialectics of Qur’anic Verses on Social Justice through Contemporary Thematic Exegesis - Ashari, Jini Resma; Hairunnisa, Rembulan; Rohmatika, Siti; Sahara, Intan; Habibuddin, Habibuddin (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
The growing social inequality and justice issues in contemporary society call for a renewed understanding of social justice values from the perspective of the Qur’an. This study aims to examine Qur’anic verses on social justice through a contemporary thematic exegesis approach, with the goal of uncovering their universal values and contextualizing them within modern social realities. Employing a qualitative method through library research, the study uses primary data from Qur’anic verses, secondary data from classical and contemporary exegesis, and tertiary data from supporting literature. Data were collected through systematic literature review and thematically classified, then analyzed by integrating the meaning of the verses with both historical contexts and present-day relevance.The findings reveal that the Qur’an outlines comprehensive principles of social justice, including wealth distribution, protection of vulnerable groups, fair law enforcement, and collective responsibility. These verses, when approached thematically, form a dialectic between the Qur’anic text and social reality, where the text provides normative guidance and reality serves as the space for its actualization. Consequently, Qur’anic principles of justice are both normative and operational, providing a basis for public policy, social ethics, and community empowerment. Thematic exegesis thus proves relevant in addressing contemporary challenges such as inequality, injustice, marginalization, and the need for inclusive social ethics in plural modern societies.